Calidad de la Atención Medica: ¿ Paciente o cliente? - CABELLO MORALES, Emilio (Revista Médica Herediana, 2015)
Result a paradox, find greater insatisfaction of the patients to their doctor, even though to the great tecnological advances in the medical field that offer best resources for the diagnostic and treatment and the reformes of modernizing of the Health Area. This fact is explained, for a preponderant preoccupation in the optimization of the tangible resources and a great carelessness for strenghen and impel the intangible resources like the “Medical Spirit” the “Institutional Spirit” and the Doctrine identified with the human factor. Therefore it is important the rol that must take on the Universities that form doctors with ethical, humanistic, cultural and scientific base such as recuperation and fortifying of the doctor-patient relation